Modelování kvality života u osob se zdravotním postižením v kontextu regionálních strategických dokumentů - Jirava, Pavel; Mandys, Jan; Křupka Jiří; Kašparová, Miloslava (Univerzita Pardubice, 2010)
The paper describes the possibilities of using methods of data-mining (modeling) in the planning and development of social policies aimed at helping persons with disabilities. Quality of life is one of the basic indicators, which helps to guide the actions of regional management in social services in the creation of local strategic documents.
Keywords: quality of life; health disability; public administration; modeling